2018
DOI: 10.1177/2332858417750376
|View full text |Cite|
|
Sign up to set email alerts
|

Prevention and Treatment of Problem Behaviors in Young Children: Clinical Implications From a Randomized Controlled Trial of BEST in CLASS

Abstract: The prevention science approach to emotional/behavioral disorders (EBD) focuses on early intervention targeting risk and resilience factors (e.g., early problem behaviors, teacher-child interactions, classroom climate). The current study investigates the effectiveness of BEST in CLASS, a classroom-based indicated preventive intervention targeting young children at risk for EBD, in terms of producing clinically meaningful reductions of problem behaviors and improvements in social skills. A total of 185 early ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 64 publications
0
19
0
3
Order By: Relevance
“…Previous research on BEST in CLASS has demonstrated positive outcomes for teachers (Conroy, Sutherland, et al, 2019) and children (Conroy et al, 2018; Sutherland, Conroy, Algina, et al, 2018) in early childhood settings. To illustrate, Conroy, Sutherland, et al (2019) found that teachers in the BEST in CLASS condition had increased self-efficacy ( ES range = 0.50–0.78) and Classroom Assessment Scoring System (CLASS; Pianta et al, 2008) domain scores ( ES range = 0.47–0.65).…”
Section: Overview Of Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research on BEST in CLASS has demonstrated positive outcomes for teachers (Conroy, Sutherland, et al, 2019) and children (Conroy et al, 2018; Sutherland, Conroy, Algina, et al, 2018) in early childhood settings. To illustrate, Conroy, Sutherland, et al (2019) found that teachers in the BEST in CLASS condition had increased self-efficacy ( ES range = 0.50–0.78) and Classroom Assessment Scoring System (CLASS; Pianta et al, 2008) domain scores ( ES range = 0.47–0.65).…”
Section: Overview Of Current Studymentioning
confidence: 99%
“…Through funding from the U.S. Department of Education, Institute of Education Sciences, BEST in CLASS-E was designed to increase positive teacher–student interactions and increase learning opportunities for students in kindergarten to grade 3 who are at risk of or with EBD. Adapted from the original BEST in CLASS for delivery in early childhood classrooms (see Conroy et al, 2018), BEST in CLASS-E was founded on Sameroff’s (2009) transactional theory, which when applied to interactions between students and teachers postulates that student behavior (whether positive or negative) influences the behavior of teachers and vice versa. These transactions between teacher and student influence, and are influenced by, the broader ecology within the classroom (Bronfenbrenner, 1979).…”
Section: Overview Of Best In Class-ementioning
confidence: 99%
“…A consistent theme of the meeting and the papers by Clarke et al (2017), Conroy et al (2018), and Lewis et al (2017) is the need for early and sustained intervention and service delivery for learners with or at risk for disabilities. A core component of this type of delivery model involves a treat then test approach.…”
Section: Discussionmentioning
confidence: 96%
“…The next two empirical articles, by Clarke et al (2017) and Conroy, Sutherland, Algina, Werch, and Ladwig (2018), address two critical needs identified in the article by Lewis and colleagues (2017) for increased attention to prevention and early intervention and more research on the impact of Tier II targeted interventions for learners with or at risk for disabilities. Clarke and colleagues highlight results from a randomized controlled trial investigating the efficacy of ROOTS, a Tier II whole number intervention for kindergarteners with or at risk for mathematics difficulties.…”
Section: Articles In This Special Topicmentioning
confidence: 99%
“…Estudos sobre treinamentos voltados para a Educação Infantil têm se intensificado e indicam que crianças expostas a programas de treinamento de habilidade sociais, tiveram um aumento de habilidade sociais, quando comparadas as que não participaram do treinamento (Cabezas et a., 2016;Vale et al, 2008;Marques-Pinto, 2015;Walker, 2017;Ladwig, 2018;Ssrker, 2016;Drugli, 2017;Aytar, 2017;Leech, 2018;. Buscando ampliar o conhecimento sobre o tema, o presente estudo teve como objetivo revisar sistematicamente a literatura acerca de programas de intervenção para o desenvolvimento de habilidades sociais na Educação Infantil, bem como identificar suas principais características, diferenças e semelhanças.…”
Section: Introductionunclassified